La captación ilegal de dinero en el Estado ecuatoriano año. - Guzmán García, Jonathan Mesías (2023)
Illegal recruitment ceases to be legal when the provisions of the law are violated, that is, when it is carried out by natural or legal persons who do not have the powers to do so, commit an illegal act causing willful and malicious activity, because in public law it is that is not allowed is absolutely prohibited and such activity is prohibited. Due to the behavior of the agent, the verb that directs this type of activity, and other elements discussed in criminal theory, it is necessary to define the illegal collection of money as a separate, independent, autonomous crime, different from the crime of fraud, with the which is often confused in the legal framework. The number of illegal money collectors existing in the Ecuadorian State has been identified, according to data from the Superintendency of Banks, so it is clear when determining that the regulatory entity does not recognize these collectors as legally constituted organizations, therefore the activity that he performs is totally outlawed. It is for this reason that the number of illegal collectors in Ecuador in 2020 is Twenty-one illegal collectors, while in 2021 that number increases, thus determining that there are Thirty-four illegal collectors. In the present investigation, the quantitative research methodology was used, being the most used within the social sciences, with which a series of data was obtained that allow improving the situations of certain groups, as in the present investigation the Institutions of the Financial System of Guaranda Canton, Bolívar province. The expected results of the investigation evidenced the recognition of the need to have greater control by the Superintendency of Banks to prevent possible affectations of the Institutions of the Financial System of the Guaranda Canton, Bolívar province, and to determine the legal actions to counter this illegal activity. Keywords: Illegal, deposit, Money, Control, Ecuadorian State, Finance system.